2023
DOI: 10.7759/cureus.36843
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Disparities in Colonic Diverticular Disease Hospitalizations in Patients With Morbid Obesity: A Decade-Long Joinpoint Analysis

Abstract: We aimed to describe epidemiologic trends in outcomes of colonic diverticular disease (CDD) hospitalizations in morbidly obese patients. MethodsWe searched the United States National Inpatient Sample databases from 2010 through 2019, obtained the incidence rate of morbid obesity (MO) among CDD hospitalizations, and used Joinpoint analysis to obtain trends in these rates adjusted for age and sex. Hospitalizations involving patients less than 18 years of age were excluded. Trends in mortality rate, mean length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Bae et al highlighted that MetS is strongly associated with asymptomatic CD risk, particularly in those with a larger waist circumference and BMI [27]. Ojemolon et al conducted a decade-long joinpoint analysis investigating the trends in hospitalizations for colonic diverticular disease in patients with morbid obesity and found that metabolic factors associated with morbid obesity may contribute to the development of CD and its related hospitalizations [28]. While these studies collectively provide insights into the possible link between MetS and CD, further investigation is warranted to fully elucidate the underlying mechanisms and establish the clinical implications of this relationship, particularly within the aging population.…”
Section: Discussionmentioning
confidence: 99%
“…Bae et al highlighted that MetS is strongly associated with asymptomatic CD risk, particularly in those with a larger waist circumference and BMI [27]. Ojemolon et al conducted a decade-long joinpoint analysis investigating the trends in hospitalizations for colonic diverticular disease in patients with morbid obesity and found that metabolic factors associated with morbid obesity may contribute to the development of CD and its related hospitalizations [28]. While these studies collectively provide insights into the possible link between MetS and CD, further investigation is warranted to fully elucidate the underlying mechanisms and establish the clinical implications of this relationship, particularly within the aging population.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed patient demographics and hospital-specific variables from the variables included in the NIS. We also assessed the comorbidity burden using Sundararajan's adaptation of the modified Deyo's Charlson comorbidity index (CCI), which has been used in prior Healthcare Cost and Utilization Project (HCUP) database research [6,7]. We highlighted the biodemographic trends over time for hospitalizations with EoE.…”
Section: Methodsmentioning
confidence: 99%